2014
DOI: 10.1007/s13158-014-0117-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Social Competence and the Child–Teacher Relationship using a Child-Centred Play Training Model in Hong Kong Preschools

Abstract: The purpose of this study was to examine whether a child-centred play training model, filial play therapy, enhances child-teacher relationship and thereby reduces children's internalising problems (such as anxiety/depression and withdrawal) and externalising problems (such as aggressive and destructive behaviour). Sixty teachers (n = 60) and 60 children (n = 60) in six kindergartens were invited to participate in the study. In Phase One, 30 of these teachers (n = 30) were randomly assigned a child with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Skills important in social life such as speaking, thinking, sharing, understanding the roles in life, helping each other, interacting with the environment, problem-solving are also reinforced in the play environment (Darwish, Esquivel, Houtz, & Alfonso, 2001). In addition, child-centered play techniques improve the relationship both between parents and children and between teacher and child, which also supports the social competence of children (Leung, 2015).…”
Section: Introductionmentioning
confidence: 83%
“…Skills important in social life such as speaking, thinking, sharing, understanding the roles in life, helping each other, interacting with the environment, problem-solving are also reinforced in the play environment (Darwish, Esquivel, Houtz, & Alfonso, 2001). In addition, child-centered play techniques improve the relationship both between parents and children and between teacher and child, which also supports the social competence of children (Leung, 2015).…”
Section: Introductionmentioning
confidence: 83%
“…Difficulties in any of these areas of language development and ability can result in myriad of issues for preschool children. For example, preschool youth who have trouble communicating with peers and caregivers can have difficulty regulating emotions and behaviors resulting in loneliness, low self-esteem, increased aggression, and negative social and academic outcomes (Balch & Ray, 2015; Chow & Wehby, 2019; Howard et al, 2017; Leung, 2015; Roth & Worthington, 2015). Preschool children particularly need opportunities to practice pragmatic language along with social and behavioral aspects through developmentally and contextually familiar means such as play for positive long-term functional outcomes (Boyd et al, 2018; Parsons et al, 2019).…”
Section: Communication Considerationsmentioning
confidence: 99%
“…Landreth and Bratton (2006) further developed parental training in play therapy with Child Parent Relationship Therapy (CPRT) which outlined a 10-session process of training, play therapy, and supervision. Filial therapy and CPRT have resulted in beneficial outcomes including improved self-concept, positive social skills, and reduced internalizing and externalizing behaviors following as few as ten sessions (Leung, 2015; Siu, 2014). Utilizing such play therapy concepts can also assist in setting a more welcoming and reassuring environment as well as aiding in communication patterns between a child and caregiver (Barimani et al, 2018; Muro et al, 2017).…”
Section: Relationship Play Therapy Interventionsmentioning
confidence: 99%
“…The filial play-therapy model is rooted in an understanding that play is a natural, developmentally appropriate form of communication and expression for children (Bratton et al, 2005; Cornett, 2012; Jones, Rhine, & Bratton, 2002; Ray, Armstrong, Balkin, & Jayne, 2015; Reddy, Files-Hall, & Schaefer, 2017; Van Fleet, 2005). It has humanistic origins, drawing from Carl Rogers’s work (Blanco & Ray, 2011; Meany-Walen & Teeling, 2016; Ray et al, 2015; Reddy et al, 2017) and evolving out of Virginia Axeline’s child-centered play therapy (CCPT; Bratton et al, 2005; Cornett, 2012; Cornett & Bratton, 2014; Leung, 2015; Lindo et al, 2014; Jones et al, 2002), which is perhaps the most widely acknowledged, researched and empirically supported form of play therapy.…”
Section: Background Literaturementioning
confidence: 99%
“…Bernard and Louise Guerney developed a method for training parents to engage in CCPT sessions with their own children (Guerney & Ryan, 2013), referred to as "special play sessions," in response to a drastic shortage of mental health professionals and an understanding of the importance of working with the child as well as the child's family (Bratton et al, 2005). In earlier studies, researchers reported a reduction in the child's emotional and behavioral symptoms and the amount of time spent in treatment; improvements in the parent-child relationship, an increased level of parental confidence, empathy, and satisfaction with their own children, and perceived improvement in parental capacity (Bratton et al, 2005;Cornett & Bratton, 2014;Jones et al, 2002;Leung, 2015;Van Fleet, 2005). More recent studies have shown that play therapy has a significant impact on a range of outcomes (Jensen, Biesen, & Graham, 2017) and that CCPT has greater benefits for children younger than age 8 from non-Caucasian backgrounds (Lin & Bratton, 2015).…”
Section: Filial Play Therapymentioning
confidence: 99%